Impact of Temperature Regimes on Germination and Seed Quality Attributes in Ajwain (Trachyspermum ammi L.) - SS SAKHARE; AH RATHOD; MP WANKHADE; AM MISAL; MG PATIL (Seed Research, 2025)
The present investigation was carried out to study the effect of different temperature on seed germination and seed quality parameters of ajwain. The laboratory experiment was laid out in Completely Randomized Design with two genotypes of Ajwain variety i.e Local and AA-1-19, four temperature treatments T1: 10oC, T2: 20oC, T3: 30oC and T4: 40oC and three replications. Observations were recorded on following characters viz first count (%), germination (%), root length (cm), shoot length (cm), seedling length (cm), seedling fresh weight (mg), seedling dry weight (mg), seedling vigour index-I, seedling vigour index-II. It was observed in the present study that the seeds should be tested at the temperature ranging around 200C to 300C. As all the parameters were maximum at this temperature range and among two varieties the variety AA-1-19 showed better response for above objectives as compared to Local.